Excange Rate Fluctuation and Real Sector Performance in Nigeria: A Disaggregated Analysis - Olajide Emmanuel Falana (European Scientific Journal, ESJ, 2019)
The Nigerian real sector is facing serious challenges due to exchange rate volatility. All the past efforts of the Central Bank of Nigeria to make naira have high international competitiveness had not yielded much result. In view of this, this study investigates the relationship between exchange rate fluctuation and the performance of the real sector in Nigeria while looking at disaggregated components of agricultural, industrial, building and construction, wholesale and retail trade, and services with a scope spanning thirty-two years, covering the period from the commencement of SAP in 1986 up to 2017. The study adopts the modified Mundell-Fleming IS-LM framework using Autoregressive Distributed Lag (ARDL) technique. The bounds tests suggest that the variables of interest are bound together in the long run with the aggregate real output (the dependent variable). This same pattern exists between the sectoral outputs and their independent variables, with the exception of Agriculture Output. The study also reveals a long-term inverse and significant relationship between exchange rate and both aggregate output and the outputs of each of the five sectors of the Nigeria real economy. The study further establishes that the sectors of the economy responded heterogeneously to exchange rate change. However, the pattern of each sector’s response to exchange rate change is far from pure homogeneity, affirming the disparity in terms of size, magnitude. The major implication of the findings is that exchange rate strategies adopted by government could not spur the desired improvement in the performance of real sector in Nigeria. The study, therefore, recommends that the monetary authorities should re-assess, monitor, and enforce the existing exchange rate policies in Nigeria with a view to stimulating increased performance of the real sector of the economy. The government should also develop an extensive programme of development of domestic industries to stimulate exports, cut non-productive imports, and create employment. There is also the need to put in place and implement coordinated macroeconomic policies that would attract foreign private investment, reduce poverty level, and stimulate exchange rate stability.